Penggunaan Budaya Pop Korea dalam Proses Pembelajaran Bahasa Korea bagi Mahasiswa dengan Gaya Belajar Campuran - Ummul Hasanah; Mery Kharismawati (JLA (Jurnal Lingua Applicata), 2019)
Many students learn Korean language because they love Korean pop culture such as song, movie, and TV show at the first place. To achieve learning goals, lecturer must match the class activities to students’ learning style. The purpose of this research is to find out the effectiveness of Korean pop culture usage in Korean language learning activities. Beside that, to find what kind of class activities gain interest to Korean language learners. By using questionnaire and observation method, it is found that Korean language students like visual learning style and the combination of visual, auditory, and kinesthetic learning style. However, there are also some students who cannot decide their own learning style. With the mixed learning style, students are more flexible to follow learning activities and can adapt easier when learning environment changes. Although most respondents support the use of Korean pop culture in the class activities, some students state their disagreement. The reasons for their disagreement are because they worry that learning atmosphere will be disturbed because the class will be too noisy and they also want to differentiate between learning in the class and enjoying Korean pop culture outside classroom.